Writing beyond pen and parchment: inscribed objects in medieval European literature - Wagner, Ricarda; Neufeld, Christine; Lieb, Ludger (Materiale Textkulturen, 2019)
Frontmatter -- Acknowledgements -- Contents -- Introduction / Wagner, Ricarda / Neufeld, Christine -- Literary Inscriptions Across Europe -- Writing Between Stillness And Movement: Script-Bearing Artefacts In Courtly German Literature / Ott, Michael R. / Velte, Laura -- Inscriptions In Old Norse Literature / Schulz, Katja -- Inscriptions In British Literature: From Runes To The Rise Of Public Poetry / Wagner, Ricarda / Neufeld, Christine -- Old French Narrated Inscriptions / Schultz, Sascha A. / Roebling-Grau, Iris -- Inscriptions In Italian Literature / De Roberto, Elisa -- Inscriptions On The Iberian Peninsula: Material Script And Narrative Logic In Castilian And Catalan Literatures / Béreiziat-Lang, Stephanie -- Materials -- Culture In Nature: Writing On Wood / Ott, Michael R. -- Inscriptions On Stone / Schultz, Sascha A. -- From Tattoo To Stigma: Writing On Body And Skin / Ott, Michael R. / Béreiziat-Lang, Stephanie -- Woven Words, Embroidered Stories: Inscriptions On Textiles / Lieb, Ludger -- Artefacts -- Writing Spaces: Inscriptions On Architecture / Neufeld, Christine -- Tablets And The Poetics Of The Premodern Post-It / Wagner, Ricarda -- Sepulchral Representation: Inscribed Tombs And Narrated Epitaphs In The High Middle Ages / Velte, Laura -- Text-Bearing Warriors: Inscriptions On Weapons / Ott, Michael R. -- More Than Bling: Inscribed Jewellery Between Social Distinction, Amatory Gift-Giving, And Spiritual Practice / Witt, Christoph -- A Cabinet Of Curiosities -- A Cabinet Of Curiosities / Wagner, Ricarda -- Indices